The Sequel Of Advanced Maternal Age On Regulation Of Anti- Mullerian Hormone, Quality Of Oocytes, Embryo Competency And Pregnancy Outcomes In Intracytoplasmic Sperm Injection Cycles - Remanan, Anu; M Murugan, M Murugan (Journal of Neonatal Surgery, 2025)
Advanced maternal age (AMA), defined as 35 years or older, significantly affects fertility due to diminished ovarian reserve (DOR), reduced oocyte quality, and decreased embryo competency. With a growing trend of delayed childbearing, AMA has become a key factor in the increasing demand for assisted reproductive technology (ART). This study aims to assess the impact of AMA on anti-Mullerian hormone (AMH) levels, oocyte quality, embryo competence, and pregnancy outcomes in intracytoplasmic sperm injection (ICSI) cycles. This retrospective study involved 240 women undergoing ICSI cycles at the Bliss Fertility Centre in Kottayam, Kerala, between January 2022 and August 2024. Participants were categorized into five age groups, and data were collected on AMH levels, oocyte quality, embryo grade, and pregnancy outcomes. AMH levels were measured using chemiluminescence immune assays, and oocyte morphology was assessed microscopically. Statistical analyses included logistic regression and chi-square tests. The mean AMH level across the cohort was 2.83 2.05 ng/mL, with significantly lower levels observed in women aged 37 years. Good-quality oocytes were retrieved in 88.4% of women aged 25–31, but only 43.2% of those aged 37 ( 0.05). Embryo competency, measured by the percentage of good-quality embryos, was not significantly different across age groups ( 0.808). Pregnancy outcomes declined with increasing age; women aged 25–31 had a 68.4% positive outcome rate, compared to 27% in women aged 37 ( ). Logistic regression highlighted that younger maternal age significantly increased the odds of achieving positive outcomes (OR: 5.85; 95% CI: 2.51–13.61). This study highlights the urgent need for early fertility interventions and ART strategies for AMA patients to optimize reproductive outcomes